English outside the academic sphere: A mobile‐based context‐aware comparison study on collaborative and individual learning. - Lin, Chih‐Chung; Barrett, Neil E.; Liu, Gi‐Zen (Journal of Computer Assisted Learning, 2021)
Context‐aware ubiquitous learning (CAUL) technology provides language learners with interactive learning environments and has been found to increase learning effectiveness and self‐efficacy due to student interaction, discussion and evaluation of the entire learning process. This study used a mobile‐based ubiquitous learning system combined with a collaborative learning approach to develop Fitness‐specific English listening and reading, and fitness knowledge. The researchers recruited two groups of participants, an individual learning group (N = 31) and a collaborative learning group (N = 30), and evaluated their learning performance via pre‐and post‐tests. In addition, a questionnaire explored the perceived usefulness, usability, follow‐up intention of using the system and self‐efficacy regarding fitness‐specific English. The results show that both groups improved fitness‐specific English in terms of listening and reading comprehension. Moreover, collaborative learning was found to facilitate fitness‐specific knowledge, and those in the collaborative learning group improved their self‐efficacy more than those in the individual learning group. Lay Description: What is already known about this topic: Computer assisted ubiquitous language learning (CAULL) can assist English learners in developing receptive language skills.CAULL has been successfully applied in various authentic learning environments including university campuses, a fitness centre and a green technology building.CAULL has been accepted by university undergraduates as an effective, interesting and motivating learning system. What this paper adds: A Fitness‐based English ubiquitous learning (FBEUL) system was successfully adapted for collaborative learning.Collaborative learning is as effective or more effective than individual learning for developing receptive English skills and subject (fitness‐based) knowledge.The collaborative learning group improved their fitness‐based self‐efficacy significantly more than the individual learning group. Implications for practice and/or policy: A collaborative learning approach can be successfully integrated into CAULL to cultivate ESP listening and reading comprehension, and subject‐specific knowledge.Collaborative learning in a CAULL environment promotes student self‐efficacy which may result in better learning outcomes and increased autonomy.System designers and ESP instructor can apply the CAULL system to other environments to motivate students and develop authentic language.